2022
DOI: 10.7717/peerj.14110
|View full text |Cite
|
Sign up to set email alerts
|

Tubular epithelial progenitors are excreted in urine during recovery from severe acute kidney injury and are able to expand and differentiate in vitro

Abstract: Background Acute kidney injury (AKI) is a serious condition associated with chronic kidney disease, dialysis requirement and a high risk of death. However, there are specialized repair mechanisms for the nephron, and migrated committed progenitor cells are the key players. Previous work has described a positive association between renal recovery and the excretion of tubular progenitor cells in the urine of kidney transplant recipients. The aim of this work was to describe such structures in non-transplanted AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous authors have used dual immunocytochemistry to identify the origin of decoy cells and whether they originate from the ureterorenal region or urinary bladder [14]. We used AQP1 as a marker for proximal tubular cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have used dual immunocytochemistry to identify the origin of decoy cells and whether they originate from the ureterorenal region or urinary bladder [14]. We used AQP1 as a marker for proximal tubular cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies have explicitly explored the utility of RPC in human urine for the early diagnosis and risk stratification of CKD [4]. Recent studies have shown that excretion rate of RPC in urine of patients with kidney transplanted AKI and with stage 3 non-transplanted AKI indicated kidney function recovery [68][69][70]. The increased number of RPC in urine might indicate an attempt of tissue regeneration, which may turn out to be an unsuccessful process resulting in further CKD progression [68][69][70].…”
Section: Urine Renal Progenitors To Explore Aki Recovery and Its Outcomementioning
confidence: 99%
“…Recent studies have shown that excretion rate of RPC in urine of patients with kidney transplanted AKI and with stage 3 non-transplanted AKI indicated kidney function recovery [68][69][70]. The increased number of RPC in urine might indicate an attempt of tissue regeneration, which may turn out to be an unsuccessful process resulting in further CKD progression [68][69][70]. Overall, RPC in urine might provide insight into the severity of kidney damage and regenerative processes after AKI, opening novel opportunities for predicting kidney function recovery and the risk of progression to CKD (shown in Fig.…”
Section: Urine Renal Progenitors To Explore Aki Recovery and Its Outcomementioning
confidence: 99%